KAJIAN HUKUM PENDAFTARAN TANAH SISTEMATIS LENGKAP YANG DILAKUKAN OLEH PEJABAT PEMBUAT AKTA TANAH - Agus Salim (Cross-border, 2022)
Complete Systematic Land Registration is a program launched by the government based on the concept of systematic land registration for the first time. Complete Systematic Land Registration is a land registration activity for the first time that is carried out simultaneously for all objects of land registration throughout the territory of the Republic of Indonesia in one village/kelurahan area or other name at the same level, which includes the collection of physical data and juridical data regarding one or more several Land Registration objects for registration purposes. Along the way, the Complete Systematic Land Registration program that the government has launched still has shortcomings in terms of socialization of the program in the field to the community, which indirectly raises the possibility of administrative problems to legal cases (problems) that occur. The problem that the author wants to raise in writing this legal thesis is a legal problem based on the Land Deed Maker Officer who manages land rights certificates that have been included in the Complete Systematic Land Registration program.